BIG-INVENTE, TOWARDS AN ADAPTIVE LEARNING APPROACH FOR DISTANCE EDUCATION USING DATA MINING TECHNOLOGIES AND BIG DATA - de Oliveira, Antonio Mauro Barbosa; Ramos, Ronaldo Fernandes; Oliveira, Carina Teixeira; Queiroz Neto, Eliezio Gomes (Conexões - Ciência e Tecnologia, 2015)
Nowadays, the learning systems are changing from teacher-centered to learner-centered paradigm although entire education system platforms and even traditional distance education systems continues to adopt the classical way. At this time, in order to have a higher level of education system personalization, it is necessary the upgrade of learning platforms as the theories of learning evolve. In this article, we show the evolution of the INVENTE platform since its initial conception in 2000 to the present days. The major change that must occurs in its structure is the ability to work with both paradigm using machine learning techniques for modeling the student and allowing the content construction from the huge collections of data available in the web, more exactly in the big data context. The challenge of the BIG-INVENTE is to use these technologies (data mining and big data) in order to customize and make more efficient the learning process.